Exchange Rate Determination: Mixed Microstructural and Macroeconomic Approach - Trabelsi Karoui, Ali; Kammoun, Aida (International Journal of Economics and Financial Issues, 2021)
This paper represents a new approach in the exchange rate determination by using microstructural and macroeconomic variables. We test a combination of fundamentals and microstructure variables in cointegrated relationship of the USD/JPY and USD/GBP currencies’ pairs. The ‘twofold’ model includes interest rate, money supply and net foreign assets as fundamentals, and spread and high-low spread as a microstructure variable. Then we compare the different models of macroeconomic and twofold model with the random walk using an error-correction method. We find that the twofold model outperforms the random structural model in out-of-sample and in-sample forecast test for both exchange rates. Twofold model outperforms in out-of-sample forecast the random walk test for the USD/JPY. Keywords: exchange rate, spreads, interest rate, money supply, net foreign assets, twofold model, cointegration JEL Classifications: G15, G17, G18, F31, F62 DOI: https://doi.org/10.32479/ijefi.11305